Conditions for Efficient Cooperation of Crisis Management Entities on the Example of a Traffic Disaster Simulation Exercise - Jaszczur, Wiesław; Noga, Henryk (Roczniki Nauk Społecznych, 2024)
The research report, based on an exercise (simulation), based on an exercise (simulation), presents the conditions and possibilities of efficient cooperation of crisis management entities in the event of a mass event, in this case a transport disaster. The scope in which ZK entities, in accordance with their procedures and principles, standards and developed good coexistence practice, implement statutory tasks in rescue operations, which are divided into rescue and procedural activities, was discussed. The exercises carried out with the participation of all (application) ZK entities in the situation of identifying a road safety threat formulated as a mass traffic accident were an integral part of the scientific project. Taking into account the empirical research carried out, proposals were presented to improve the process of cooperation between crisis management entities. The aim of the research was to diagnose the limitations of efficient cooperation of ZK entities and to formulate conditions and proposals for improving this cooperation.